Paediatric calcified tendinitis in extensor carpi radialis brevis: A case report - Firas Ahmad Suleiman; Ahmad Al-Marzouq; Razi Altarawneh; Haider Saudi; Ashraf Otom (Journal of the Pakistan Medical Association, 2020)
Paediatric calcified tendinitis is a rare entity. Although trauma is a triggering factor, the aetiology is unknown. Conservative management is the treatment of choice with most patients experiencing symptom resolution within six weeks. We describe the case of a six-year-old male child with persistent wrist pain despite conservative treatment. Exploration revealed involvement of the extensor carpi radialis brevis, and complete recovery after surgical excision of the lesion identified on X-ray. Keywords: Paediatric, Calcified tendinitis, Extensor carpi radialis brevis.